Integrasi Program Dakwah dan Budaya: Studi Etnografi Virtual Mediamorfosis Radio Nada FM Sumenep Madura - Achmad, Zainal Abidin (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2019)
This article examines how the pattern of mediamorfosis of Nada FM Radio Sumenep, particularly in regard to the integration between Islamic preaching programs and Madura cultural programs as well as the form of interaction between listeners and radio institutions within a networked society. This article resulted from qualitative research using virtual ethnography. The findings revealed that the pattern of mediamorfosis using streaming, Facebook, Twitter, Instagram, and WhatsApp. Second, making the program aimed at strengthening Islamic religious beliefs while maintaining Madura culture. Third, connectivity in a networked society makes the communication of the parties equal, intimate and open to the public. Forth, listeners prefer to use WhatsApp to express criticism, including with regard to the suitability of the da'wah theme and the choice of social media.